Transcriptional profile features in patients with early and late preeclampsia - V. E.A. Kotelnikova; D. E. Pantyukhova; F. D. Ablyamitova; S. N. Vikinskaya; Kh. U. Khalilova; L. F. Mustafaeva; D. A. Barieva; D. V. Yarovaya; N. D. Chopik; M. S. Ermakova; L. E. Sorokina (IRBIS LLC, 2024)
Aim: to assess the molecular mechanisms in developing various clinical phenotypes of preeclampsia (PE) by analyzing specific placental tissue transcriptome patterns.   Materials and Methods. The prospective observational comparative study in parallel groups enrolled 43 pregnant women divided into 2 groups: main group - 23 pregnant women with diagnosed PE and control group - 20 apparently healthy women with uncomplicated pregnancy course, delivery and the postpartum period. To examine PE phenotypic features, the main group of pregnant women with PE was subsequently divided into 2 subgroups according to the date of pathology onset: early (n = 10) and late (n = 13) PE. Using the whole-genome next-generation sequencing (NGS), a comparative analysis of altered 18 microRNA level in placental tissue was carried out.   Results. Pregnant women with early PE compared to the control group were characterized by significantly low expression level for hsa-miR-656-3p (p < 0.001), hsa-miR-323a-5p (p = 0.017), hsa-miR-519c-3p (p = 0.019), hsa-let-7i-5p (p = 0.019), hsa-miR-433-3p (p = 0.019), hsa-let-7g-5p (p = 0.030), hsa-miR-214-5p (p = 0.030), hsa-miR-27a-5p (p = 0.031), hsa-miR-339-5p (p = 0.041), hsa-miR-524-5p (p = 0.045), hsa-miR-1283 (p = 0.049) and high expression for hsa-miR-151a-5p (p = 0.007), hsa-miR-4521 (p = 0.018), hsa-miR-30d-5p (p = 0.026), hsa-miR-548l (p = 0.027), hsa-miR-133b (p = 0.034), hsa-miR-424-5p (p = 0.042), hsa-miR-211-5p (p = 0.049). Patients with late PE had significantly decreased expression for hsa-miR-656-3p (p = 0.050) andhsa-miR-574-3p (p = 0.017) as well as a significantly higher for hsa-miR-211-5p (p = 0.001) compared to the control group. Subgroup of women with early vs. late onset PE was characterized by significantly decreased expression level for hsa-miR-323-5p (p = 0.007) and overexpressed hsa-miR-30d-5p (p = 0.002), hsa-miR-5481 (p = 0.027).   Conclusion. The noted multidirectional expression for some microRNAs in subgroups of PE patients confirms the validity for stratification of such pathology based on two distinct phenotypic manifestations (early and late forms) and indicates the existence of different pathophysiological vectors in PE formation.